Noise Pollution at Health Care Centers in Mymensingh City of Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
The study was conducted at the health care centers in Mymensingh city of Bangladesh during the period from March 2015 to November 2015 to find out the level of noise pollution and its severity to the associated health effects. In the study, time-weighted average noise levels were measured at indoor and outdoor of three hospitals namely Mymensingh Medical College and Hospital, Rajdhani Hospital (Pvt.) Limited and Shawdesh Hospital (Pvt.) Limited and two clinics such as Popular Diagnostic Centre Ltd, Safeway Diagnostic Centre Ltd. of Mymensingh city. The highest noise level was found in Mymensingh Medical College and Hospital and the lowest level was found in Shawdesh Hospital (Pvt.) Limited, Sarda Gosh Road. All of these noise levels were exceeded the acceptable limit of 45 dB set by the Department of Environment (DoE), Government of Bangladesh. Simultaneously a survey study was conducted with doctors, students, nurse/staff and patients. Most of the common problems occurred from noise pollution were identified as conversation, headache, hearing problems, and increased heartbeat. To resolve the problem 28% of the respondents suggested for sound harriers, 25% suggested for awareness of doctors, 22% suggested for awareness of visitors, 13% suggested for controlling visitors and 4% suggested for banning of hydraulic horn. However, the role of NGOs, researchers and professionals, media and concerned individuals is significant in minimizing the environmental hazards of noise pollution.J. Environ. Sci. & Natural Resources, 9(1): 87-90 2016